KOMBINASI BAHAN ORGANIK (RASIO C:N) PADA PENGOLAHAN LUMPUR (SLUDGE) LIMBAH PENCELUPAN - Ary Pramaswari, Ida Ayu; Budiarsa Suyasa, I Wayan; Bawa Putra, Anak Agung (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 1 Januari 2011, 2012)
A research on the Combination of Organic Matter (the ratio of C:N) in the Sludge Treatment of dying waste has been conducted. The sludge was mixed with organic matter wich were dried leaves and dung in various compositions. The compositions (sludge : organic matter) made were 3 : 7, 1 : 1, and 7 : 1. In this research it was found that the first composition contained the highest organic matter (the lowest C : N = 28.05/1) and showed the best effect to the composting process indicated by physical characteristics. The Compost with the lowest ratio C:N (17,71/1) gave the best total N, organic C, available K, and available P contents which were 0.98%; 17.90 %; 22,092.1894 ppm; and 568.2312 ppm respectively. All composts had organic C and total N that meet the SNI 19-7030-2004, and high available P and K contents. These were in agreement to the evaluation of fertility analysis. More over, all compost showed physical caracteristic such as temperature, colour, texture, and odour that are in agreement to those of SNI 19-7030-2004. Unfortunately the pH did not meet the SNI 19-7030-2004.
Keywords: Ratio C:N, dyed waste, compost